Спектрофотометричне визначення оригінальної субстанції Хінабут і таблетованої лікарської форми на її основі - Воскобойнік, Олексій Юрійович; Медведєва, К. П.; Коваленко, Сергій Іванович; Васюк, Світлана Олександрівна; Воскобойник, А. Ю.; Медведева, Е. П.; Коваленко, С. И.; Васюк, С. А.; Voskoboynik, O. Yu.; Medvedeva, K. P.; Kovalenko, S. I.; Vasyuk, S. O. (Запорізький державний медичний університет, 2016)
Мета роботи – розроблення високочутливої, простої у виконанні й валідної спектрофотометричної методики кількісного визначення оригінальної субстанції Хінабут і таблетованої лікарської форми на її основі. Коректність і правильність методики, котра запропонована для виконання запланованих завдань, доведені шляхом здійснення стандартизованої процедури валідації. Числові показники лінійної залежності, котрі одержані згідно з Державною Фармакопеєю України (ДФУ) (коефіцієнт кореляції r, залишкова сума квадратів відхилень sy, вільний член лінійної регресії а), відповідають всім вимогам щодо параметрів лінійної залежності. Встановлення прецизійності та правильності методики показало її відповідність до вимог ДФУ. Для підтвердження коректності методики при відтворюванні в іншій лабораторії визначили прогноз повної невизначеності методики. Показали, що методика даватиме коректні результати й в інших лабораторіях. Цель работы – разработка высокочувствительной, простой в исполнении и валидной спектрофотометрической методики количественного определения оригинальной субстанции Хинабут и таблетированной лекарственной формы на её основе. Корректность и пригодность предложенной методики для выполнения запланированных заданий доказаны путём проведения стандартизированной процедуры валидации. Полученные согласно Государственной Фармакопее Украины (ГФУ) числовые показатели линейной зависимости (коэффициент к орреляции r, остаточная сумма квадратов отклонений sy, свободный член линейной регрессии а) соответствуют всем требованиям относительно параметров линейной зависимости. Установление прецизионности и правильности методики показало её соответствие требованиям ГФУ. Для подтверждения корректности методики при воспроизводимости в других лабораториях определён прогноз полной неопределённости методики. Показано, что методика будет давать корректные результаты в других лабораториях. Aim. The sensitive, effi cient and express method for original active pharmaceutical ingredient Quinabut determination and based on it tablets was described in presented article. Methods and results. Detailed analysis of physicochemical properties of studied compound conducted by authors allowed to substantiate the usage of purifi ed water as solvent. It was shown, that UV-spectra of active pharmaceutical ingredient was characterized by absorption maximum at 232 nm. Length wave mentioned above was used for further studies. The elaborated method is based on evaluation of proper absorption of active pharmaceutical ingredient solution, data of absorption of studied sample and standard solution was used for calculation of the fi nal results. Conclusions. Correctness and suitableness of proposed method for realization of planned tasks were proven by conduction of standardized validation procedure. The evaluation of linearity was conducted in range of concentration wherein the compliance with Beer law was observed. Indexes of linear dependence, that were obtained according to SPhU recommendations (correlation coeffi cient r, residual sum of deviation squares, free term of linear regression) were in compliance with requirements for linear dependence parameters. Conducted evaluation of precision and accuracy of method showed it compliance with requirements of SPhU. The prediction of total irreproducibility was conducted for confi rmation of method correctness by repeating in other laboratories. It was shown that proposed method would produce correct results in other laboratories.
Спектрофотометрическое определение оригинальной субстанции Хинабут и таблетированной лекарственной формы на её основе
Spectrophotometric determination of original active pharmaceutical ingredient Quinabut and tablets based on it
Keywords: натрію 4-(3-метил-2-оксо-2H-[1,2,4]триазино[2,3-c]хіназолін-6-іл)бутаноат; Хінабут; субстанція; таблетки; аналіз; спектрофотометрія; натрия 4-(3-метил-2-оксо-2H-[1,2,4]триазино[2,3-c]хиназолин-6-ил)бутаноат; Хинабут; субстанция; анализ; спектрофотометрия; Sodium 4-(3-methyl-2-оxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)butanoate; Quinabute; Substance; Tablets; Analysis; Spectrophotometry